2015
DOI: 10.7567/jjap.54.021301
|View full text |Cite
|
Sign up to set email alerts
|

Marked increase in photoluminescence from porous Si aged in ethanol solution

Abstract: Photoluminescence properties of porous Si aged in ethanol solution and porous Si films aged in ambient air were studied. It was shown that the photoluminescence properties of porous Si strongly depend on aging time and environmental conditions. The photoluminescence intensity of porous Si dispersed in ethanol solution increases 50-fold with aging for 7 d. This increase is accompanied by increases in Si–O bond density and lifetime, indicating that the electron–hole pair is strongly confined by the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The emission decays for all the samples studied here were found to fit reasonably well to an exponential function. 33 As seen previously for porous Si, the decay time constants (s) were on the order of tens of microseconds, and each sample showed a pronounced increase in s with increasing emission wavelength, in accordance with the quantum-confinement model ( Fig. 4 and Table II).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The emission decays for all the samples studied here were found to fit reasonably well to an exponential function. 33 As seen previously for porous Si, the decay time constants (s) were on the order of tens of microseconds, and each sample showed a pronounced increase in s with increasing emission wavelength, in accordance with the quantum-confinement model ( Fig. 4 and Table II).…”
supporting
confidence: 89%
“…The fact that the air-dried samples are exposed to oxygen implies that their surface may become oxidized during the drying process. Oxidation-derived passivation of surface defects is known to reduce non-radiative recombination and increase QY on these types of samples, 3,33,36,37 so any differences in surface oxidation are apparently not as important in the present samples.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In the present case, we found that on the microsecond timescale the emission decays could be well fit with a single‐exponential function. The wavelength‐dependent emission lifetime (τ) values obtained from single‐exponential fits of wavelength slices extracted from the family of time‐resolved spectra (Figure e and Figure S2, Supporting Information) showed a pronounced increase in lifetime with increasing emission wavelength, ranging from 17 µs at λ em = 550 nm, to 118 µs at λ em = 850 nm . Sets of wavelength‐dependent lifetime values were captured periodically from the PSiNPs as they underwent slow dissolution in phosphate‐buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, a simple oxidation method to form a high-quality thin SiO 2 layer (with a low density of nonradiative recombination centers) on the surface of the porous Si was proposed 21 . In this method, the PL intensity of the porous Si powder increased when the porous Si was dispersed in an ethanol solution and aged for several days.…”
Section: Introductionmentioning
confidence: 99%